Towards a better conceptual understanding of how students learn business research methods - Kueenzi, Stefan (Journal of Management and Business Education, 2023)
Business graduates need a solid understanding of research methods, for example to make decisions based on empirical evidence. As a meta-analytic review by Earley (2014) shows, we are lacking sufficient empirical information on what influences research methods education and a solid conceptual understanding of what these influential factors mean for student learning. This research begins to fill this gap by presenting results from interviewing 18 lecturers in undergraduate programmes in Business and Management. The findings are linked to Paul R. Pintrich’s framework for assessing motivation and self-regulated learning (Pintrich, 2004). The major findings include that aspects related to why students are doing specific learning tasks and the concept of self-efficacy play important roles. Other themes of the meta-analytic review by Earley are discussed, for example students’ anxiety, poor attitudes, and misconceptions about research. The study concludes by making recommendations for future research.